2010
DOI: 10.1061/(asce)gm.1943-5622.0000062
|View full text |Cite|
|
Sign up to set email alerts
|

Measuring and Modeling Proportion-Dependent Stress-Strain Behavior of EPS-SandMixture

Abstract: A geofoam was produced by blending expanded polystyrene (EPS) beads and sands in proportions. The formed mixtures, known as EPS-sands, were 32-66% lighter than general earthfills (e.g., sand). Consolidated-drained (CD) triaxial compression tests were conducted on EPS-sand mixture specimens to observe their stress-strain characteristics, specifically, the stress-strain responses in relation to the EPS contents (0.5%, 1.5% and 2.5% by weight) used in the mixtures and confining pressures

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 61 publications
(20 citation statements)
references
References 23 publications
0
20
0
Order By: Relevance
“…A combination of cement and air foam has been recently researched and applied in civil engineering and infrastructure applications as fill and pavement materials to primarily reduce the load on soft clay deposits (Tsuchida, 1995;Tsuchida et al, 1996;Tsuchida et al, 2001;Tsuchida and Kang, 2002;Tsuchida and Kang, 2003) similar to other lightweight fill materials such as expanded polystyrene (Deng and Xiao, 2010), tires (Nakhaei et al, 2012) and lightweight concrete (Chindaprasirt and Rattanasak, 2011). This stabilized material is designated as Lightweight Cellular Cemented (LCC) material (Horpibulsuk et al, 2014a).…”
Section: Introductionmentioning
confidence: 98%
“…A combination of cement and air foam has been recently researched and applied in civil engineering and infrastructure applications as fill and pavement materials to primarily reduce the load on soft clay deposits (Tsuchida, 1995;Tsuchida et al, 1996;Tsuchida et al, 2001;Tsuchida and Kang, 2002;Tsuchida and Kang, 2003) similar to other lightweight fill materials such as expanded polystyrene (Deng and Xiao, 2010), tires (Nakhaei et al, 2012) and lightweight concrete (Chindaprasirt and Rattanasak, 2011). This stabilized material is designated as Lightweight Cellular Cemented (LCC) material (Horpibulsuk et al, 2014a).…”
Section: Introductionmentioning
confidence: 98%
“…The behaviour is essentially dependent on the mix ratios and mechanical interaction of sands and beads. 12 The reduction of lateral earth forces acting on non-yielding retaining walls by EPS inclusion was also investigated. 13 It was observed that the deformation of the EPS was concentrated in the bottom half of the retaining wall because of higher stresses in that zone.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Previous studies show that the EPS content greatly affects the shear strength and unit weight of EPS-sand mixtures. The EPS-weight content of 0.5% suggested by Deng and Xiao [4] could achieve reasonable shear strength as well as a 26% reduction in unit weight. It was also recognized that the strength and deformation properties of LWGM were significantly improved due to the application of cement-like materials.…”
mentioning
confidence: 99%